(untitled) (Journal of the College of Basic Education, 2026)
The aim of the research was to identify the impact of specific exercises using artificial intelligence techniques on some functional variables and physical endurance among participants in fitness centers. The researcher adopted the experimental method with a two-equivalent group design, where the sample consisted of 24 trainees aged 25-30 years, who were divided into an experimental group and a control group. The experimental group applied an artificial intelligence training program, while the control group adhered to the regular program. The measurements included functional variables represented by pulse recovery rate, respiratory rate, anaerobic capacity, blood sugar level, lactic acid, in addition to physical endurance. The results showed statistically significant differences between the pre-test and post-test, favoring the post-test, as well as the experimental group outperforming the control group in all the variables under study. This improvement is attributed to the precise organization and regulation of the training load according to the individual response of each trainee. The study concluded that integrating artificial intelligence techniques in designing training programs contributes to enhancing physiological adaptations and improving physical performance efficiency more effectively and safely.